Development of a Fall Detection System for the Elderly - Izza Arshad, Noreen; Mehat, Mazlina; Suraya Jainlabdin, Fathin; Yu Chen, Goh (International Journal of Engineering and Technology, 2018)
Fall detection is a major challenge especially for the elderly as the decline of their physical fitness.There are various fall detection devices and smartphone applications available in the market butmany are found pricy and not feasible for elderly usage. Some free or cheap device need to be carried by the user at all times in managing falls incidents and elderly will not religiously follow that requirements. Therefore, this project aims to merge the advantages of both fall detection devices and applications.By applying the evolutionary prototyping methodology, ElderBand and ElderAlert were created to assist the elderly in detecting and managing fall incidents. ElderBand is a smart wearable which is lightweight and can be wear by the user at all times; while ElderAlert is a smartphone application which enables notifications to the emergency contacts in a case of fall incidents. ElderBand and ElderAlert accuracy were successfully tested and should be able to position the usage of smart wearable with mobile application into agrowing healthcare market.Â Â